The Effect of Workload and Training on Employee Performance (Case Study at Tikung Lamongan Islamic Junior High School) - Faris Dwi; Nurul Badriyah; Titin Titin (Sean Institute, 2025)
This study aims to determine promotion, price perception, and product diversity, to partial, simultaneous, and most dominant purchase decisions. The research method used is causal associative with a quantitative approach. The results of the study showed that promotion did not have a significant effect. Meanwhile, price perception, and product diversity have a positive and significant effect on purchasing decisions. Promotions, price perceptions, and product diversity simultaneously have a positive and significant effect on purchasing decisions. The price perception variable has the most dominant influence.